Leaded tin bronzes: the effects of casting method on dry sliding behaviour - Nyyssönen, T; Ruusila, V; Kallio, M; Vuorinen, P; Valtonen, K; Kuokkala, V-T (Tribologia - Finnish Journal of Tribology, 2012)
In metal-to-metal sliding bearing applications, leaded tin bronzes are widely known as materials with excellent seizure resistance. In conditions of boundary or dry lubrication, lead may smear across the sliding surface, preventing surface contact and catastrophic seizure. The aim of this study was to determine the effects of casting method on the dry sliding behaviour of leaded tin bronzes. Continuous cast, centrifugally cast, and sand cast leaded tin bronze samples with varying lead contents were subjected to pin-on-disk- testing. It was found that casting method has a significant effect on the wear behaviour of leaded tin bronzes in dry sliding conditions. With continuous cast samples, the dominant wear mode was rapid, stable microcracking along copper/lead interfacial boundaries. With centrifugally and sand cast samples, wear occurred more slowly and erratically through the formation of transfer layers. The dominant wear mode was found to be connected to the coarseness of the distribution of lead particles in the copper matrix.